Pendampingan Pembuatan Platform Digital Pada Usaha Mikro Kecil dan Menengah di Desa Ngijo - Mardhiyaturrositaningsih Mardhiyaturrositaningsih; Ridwan Maulana (I-Com: Indonesian Community Journal, 2024)
Micro, Small and Medium Enterprises, in addition to their great potential, also face obstacles in implementing digital marketing related to the low readiness of MSMEs to conduct online marketing. The use of digital platforms by MSMEs only reaches 8 percent. sMentoring the creation of digital platforms for Micro, Small and Medium Enterprises aims to help business actors in Ngijo Village to Go Digital. This is based on the importance of the role of digitalization in supporting the development of MSMEs. This community service activity uses the Participatory Action Research (PAR)method. This activity includes preparing to sell on Shopee, such as creating a Shopee account, filling in store information, and adding products with attractive photos and complete descriptions. In addition, the arrangement and management of the store is also a focus, including setting up a store profile, adding a bank account, and managing orders. The result of this mentoring activity is the ownership of a digital platform account by the participants who are MSMEs in Ngijo.